Patterns and profiles of drug resistance-conferring mutations in Mycobacterium tuberculosis genotypes isolated from tuberculosis-suspected attendees of spiritual holy water sites in Northwest Ethiopia - Reta, Melese Abate; Maningi, Nontuthuko Excellent; Fourie, P. Bernard (Frontiers in Public Health, 2024)
Purpose This study examined the patterns and frequency of genetic changes responsible for resistance to first-line (rifampicin and isoniazid), fluoroquinolones, and second-line injectable drugs in drug-resistant Mycobacterium tuberculosis (MTB) isolated from culture-positive pulmonary tuberculosis (PTB) symptomatic attendees of spiritual holy water sites (HWSs) in the Amhara region. Patients and methods From June 2019 to March 2020, a cross-sectional study was carried out. A total of 122 culture-positive MTB isolates from PTB-suspected attendees of HWSs in the Amhara region were evaluated for their drug resistance profiles, and characterized gene mutations conferring resistance to rifampicin (RIF), isoniazid (INH), fluoroquinolones (FLQs), and second-line injectable drugs (SLIDs) using GenoType®MTBDRplus VER2.0 and GenoType®MTBDRsl VER2.0. Drug-resistant MTB isolates were Spoligotyped following the manufacturer’s protocol. Results Genetic changes (mutations) responsible for resistance to RIF, INH, and FLQs were identified in 15/122 (12.3%), 20/122 (16.4%), and 5/20 (25%) of MTB isolates, respectively. In RIF-resistant, rpoB/Ser531Lue (n = 12, 80%) was most frequent followed by His526Tyr (6.7%). Amongst INH-resistant isolates, katG/Ser315Thr1 (n = 19, 95%) was the most frequent. Of 15 MDR-TB, the majority (n = 12, 80%) isolates had mutations at both rpoB/Ser531Leu and katG/Ser315Thr1. All 20 INH and/or RIF-resistant isolates were tested with the MTBDRsl VER 2.0, yielding 5 FLQs-resistant isolates with gene mutations at rpoB/Ser531Lue, katG/Ser315Thr1, and gyrA/Asp94Ala genes. Of 20 Spoligotyped drug-resistant MTB isolates, the majority (n = 11, 55%) and 6 (30%) were SIT149/T3-ETH and SIT21/CAS1-Kili sublineages, respectively; and they were any INH-resistant (mono-hetero/multi-). Of 15 RIF-resistant (RR/MDR-TB) isolates, 7 were SIT149/T3-ETH, while 6 were SIT21/CAS1-Kili sublineages. FLQ resistance was detected in four SIT21/CAS1-Kili lineages. Conclusion In the current study, the most common gene mutations responsible for resistance to INH, RIF, and FLQs were identified. SIT149/T3-ETH and SIT21/CAS1-Kili constitute the majority of drug-resistant TB (DR-TB) isolates. To further understand the complete spectrum of genetic changes/mutations and related genotypes, a sequencing technology is warranted.